Congress and the Supreme Court in a partisan era - Melnick, R (Foundation for Law, Justice and Society, 2007)
There are significant lessons to be learned about relations between the Court and Congress from this analysis of the past dozen years. Firstly, while the appointment and confirmation process ensures some general congruence of thinking between Justices, presidents and members of Congress, the weakness of ex post controls guarantees that substantial differences appear regularly and enduringly. Secondly, the Court highlights the serious fissures that run through American conservatism on numerous key issues, since it sees it as its duty to tackle contentious issues which are rarely debated in Congress. Finally, institutional demands inevitably influence how judges, legislators and executives view issues. Even if Republicans continue to control the White House and appoint several more reliably conservative judges to the Supreme Court, they will continue to disagree on many issues.